Kapasitas Operasional Organisasi dari Satuan Pendidikan di Kota Denpasar dalam Implementasi Kebijakan Pendidikan Inklusif - Linardi, I Gede Rama; Muluk, Mujibur Rahman Khairul; Nuh, Mohammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2026)
Inclusive education policies in Indonesia mandate equal learning opportunities for students with disabilities and marginalized backgrounds. However, implementation challenges persist, often linked to the organizational operational capacities of educational institutions. This study examines SMA Negeri 2 Denpasar (secondary level) and Universitas Warmadewa (tertiary level) in Denpasar, assessing their capacities across five indicators: organizational commitment, resource availability, internal coordination, performance management, and administrative accountability. Using qualitative methods and semi-structured interviews with 11 informants, the study found that SMA Negeri 2 Denpasar demonstrated operational capacity across all indicators, driven largely by compliance with government mandates. Conversely, Universitas Warmadewa showed partial capacity, with strengths in resources but lacking in other indicators. These findings underscore the need for more integrated and institutionalized approaches to inclusive education to improve accessibility and equity for all students.